2011
DOI: 10.1128/cvi.05159-11
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Recombinant 10-Kilodalton Immunodominant Region of the BP26 Protein of Brucella abortus for Specific Diagnosis of Bovine Brucellosis

Abstract: Brucellosis is a disease with worldwide distribution affecting animals and human beings. Brucella abortus is the causative agent of bovine brucellosis. The cross-reactions of currently available diagnostic procedures for B. abortus infection result in false-positive reactions, which make the procedures unreliable. These tests are also unable to differentiate Brucella-infected and -vaccinated animals. The present work is focused on the use of a nonlipopolysaccharide (LPS) diagnostic antigen, a recombinant 10-kD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
9
0
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 21 publications
(12 reference statements)
2
9
0
2
Order By: Relevance
“…Omp25, Omp2b and a hypothetical protein were predicted as outer membrane proteins. Another protein identified in the present work, Omp28 (also called BP26), has been described to have the diagnostic potential in bovine brucellosis by our group earlier (Tiwari et al, 2011). One of the predicted unknown proteins of this study, 31-kDa surface protein, has been shown to be protective in nature (Cassataro et al, 2005).…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…Omp25, Omp2b and a hypothetical protein were predicted as outer membrane proteins. Another protein identified in the present work, Omp28 (also called BP26), has been described to have the diagnostic potential in bovine brucellosis by our group earlier (Tiwari et al, 2011). One of the predicted unknown proteins of this study, 31-kDa surface protein, has been shown to be protective in nature (Cassataro et al, 2005).…”
Section: Discussionsupporting
confidence: 53%
“…One of the predicted unknown proteins of this study, 31-kDa surface protein, has been shown to be protective in nature (Cassataro et al, 2005). Another protein identified in the present work, Omp28 (also called BP26), has been described to have the diagnostic potential in bovine brucellosis by our group earlier (Tiwari et al, 2011). Three proteins in this study were predicted as cytoplasmic proteins.…”
Section: Discussionsupporting
confidence: 52%
“…Chaudhuri et al found that the Omp28-based ELISA showed 88.7% sensitivity and 93.8% specificity when used in the detection of bovine brucellosis (16). In 2011, Tiwari et al (28) found that the a For the detection of infection in sheep, the relative specificity and sensitivity of BP26-based i-ELISA to LPS-based i/c-ELISAs were 90% and 82.2%, respectively; (agreement) ϭ 0.5677 for the BP26-based i-ELISA and LPS-based i/c-ELISAs. For the detection in goats, the relative specificity and sensitivity of BP26-based i-ELISA to LPS-based i/c-ELISAs were 100% and 80%, respectively; ϭ 0.5246 for the BP26-based i-ELISA and LPS-based i/c-ELISAs.…”
Section: Discussionmentioning
confidence: 99%
“…The unbound reagents are removed by washing and the enzyme is allowed to interact with its substrate to yield a coloured product that is quantitatively measured by optical density or can be visualised directly. ELISA is a simple, 20,21 , Brucella abortus 22 , Ebola and Marburg viruses 23 or to detect bio-threat toxins 24 . Besides, some other variants of immunological assays like fluorescent microscopy 25,26 are also used for detection of BWAs.…”
Section: Enzyme Linked Immunosorbant Assaymentioning
confidence: 99%